BUDAYA DAN IKLIM ORGANISASI TERHADAP KINERJA KARYAWAN PERTAMINA PERSERO - Marsa Ifelda; Ifelda, Marsa Ifelda; Darma, Marchylio Naufal Safir (Journal of Professional Education, 2026)
This study aims to examine the role of organizational culture and climate on employee performance in the context of PT. Pertamina (Persero) through a systematic literature review approach. The study focuses on empirical findings regarding the relationship between organizational culture, work climate, sustainable human resource management practices, specific work behaviors, and employee performance in various units within Pertamina and similar organizations in the energy sector. Research data was obtained from journal articles and scientific documents purposively selected through identification, selection, and synthesis based on the PRISMA 2020 guidelines. The study results indicate that a strong organizational culture, characterized by the internalization of the values ​​of discipline, results orientation, cooperation, safety, and sustainability, is consistently associated with improved employee performance. Furthermore, a positive work climate and Sustainable Human Resource Management and Green Human Resource Management practices contribute to strengthening the influence of culture through the formation of productive work behaviors, compliance with safety procedures, and environmentally conscious behaviors. The synthesis of findings leads to a multi-layered conceptual framework that positions organizational culture as a fundamental determinant, work climate and HR practices as contextual reinforcers, and specific work behaviors as mediating mechanisms linking both to performance. This research provides context for developing studies of organizational behavior in state-owned energy companies and serves as a foundation for further, more comprehensive empirical research.